A synthesis of traditional project engineering management in construction projects with agile approaches towards efficiency gains - Albishri, Abdulaziz; Whyte, Andrew (Research Publishing Services, 2012)
Projects and mega projects around the world can be successfully characterised by variables of flexibility & speed of delivery; in other words agility in addressing and realising respective project brief(s) and the subsequent completion of a construction asset, as well as its effective operation and maintenance over the usable life-cycle; projects that do not, at the outset, seek to embrace a degree of flexibility are often those that result in being over-budget and overtime. Given media reports noting $7B blow-outs and 4 year delays for high profile projects locally, there is a need to address the tools and techniques of project management and their implementation, as design teams strive to deliver a quality product at a predicted cost, within a predicted timescale for construction. Agility concepts and approaches used predominately in the manufacturing industry offer effective methodological system(s) for companies seeking to win tenders and secure procurement routes. Given the attractiveness of this approach, there is opportunity to transfer this set of agile skills towards efficiency gains from manufacturing, to construction and civil engineering projects. The work here represents the very early stages in an ongoing research project into the potential of agile approaches to address concerns, locally and internationally, regarding construction industry time and budget over-runs, with future work seeking to address explicitly engineering project delivery through agility approaches.